Respostas

2014-07-13T21:25:44-03:00
Como eu resolvo a equação: 600/x-2 - 600/x = 10???

  600             600
-------   -    ---------- = 10
   x -2              x


x(600)  -   600(x-2) = 10(x(x-2))
------------------------------------
             x(x-2)                           fração com igualdade desprezamos o denominador


x(600) - 600(x-2) = 10(x(x-2))

600x - 600x + 1200 = 10(x² - 2x)
600x - 600x + 1200 = 10x² - 20x
           
      0           +1200 = 10x² - 20x

1200 = 10x² - 20x ------------------------igualar a ZERO
1200 - 10X² + 20X = 0  ------arrumar a casa

-10x² + 20x + 1200 = 0
a = - 10
b = 20
c = 1200
Δ = (20)² - 4(-10)(1200)
Δ = 400 + 48000
Δ = 48400-----------------------√48400 = 220
se
Δ > 0
então  (baskara)
x = - b - +√Δ/2a
x' = -20 - √48400/2(-10)
x' = -20 - 220/-20
x' = -240/-20 
x' = + 240/20
x' = 12
e
x" = - 20 + √48400/2(-10)
x" = - 20 + 220/-20
x" = 200/-10
x" = - 200/20
x" = - 10

V = { -10: 12}